Health Care Utilization Rates After Oregon's 2008 Medicaid Expansion: Within-Group and Between-Group Differences Over Time Among New, Returning, and Continuously Insured Enrollees. Issue 11 (November 2016) - O'Malley, Jean P.; O'Keeffe-Rosetti, Maureen; Lowe, Robert A.; Angier, Heather; Gold, Rachel; Marino, Miguel; Hatch, Brigit; Hoopes, Megan; Bailey, Steffani R.; Heintzman, John; Gallia, Charles; DeVoe, Jennifer E.
Abstract : Background: Although past research demonstrated that Medicaid expansions were associated with increased emergency department (ED) and primary care (PC) utilization, little is known about how long this increased utilization persists or whether postcoverage utilization is affected by prior insurance status. Objectives: (1) To assess changes in ED, PC, mental and behavioral health care, and specialist care visit rates among individuals gaining Medicaid over 24 months postinsurance gain; and (2) to evaluate the association of previous insurance with utilization. Methods: Using claims data, we conducted a retrospective cohort analysis of adults insured for 24 months following Oregon's 2008 Medicaid expansion. Utilization rates among 1124 new and 1587 returning enrollees were compared with those among 5126 enrollees with continuous Medicaid coverage (≥1 y preexpansion). Visit rates were adjusted for propensity score classes and geographic region. Results: PC visit rates in both newly and returning insured individuals significantly exceeded those in the continuously insured in months 4 through 12, but were not significantly elevated in the second year. In contrast, ED utilization rates were significantly higher in returning insured compared with newly or continuously insured individuals and remained elevated over time. New visits to PC and specialist care were higher among those who gained Medicaid compared with the continuously insured throughout the study period. Conclusions: Predicting the effect of insurance expansion on health care utilization should account for the prior coverage history of new enrollees. In addition, utilization of outpatient services changes with time after insurance, so expansion evaluations should allow for rate stabilization. Abstract : Supplemental Digital Content is available in the text.